2018
DOI: 10.7752/jpes.2018.03228
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction: Aging is inevitable and irreversible, but with the advancement of technology, life expectancy is increasing every year, bringing with it proposals for various interventions to improve the quality of life. One such intervention is physical exercise programs. Objective: Evaluated the functional fitness of senior female practitioners of ballroom and circular dancing. Methods: Senior women were recruited and distributed into three groups: ballroom dancing (BD, n=15); circular dancing (CD, n=16); cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This proportion should increase to 25% in the coming decade (Economic and Financial Affairs, 2018). Regular physical activity (PA) is considered a basic element of healthy and independent ageing (Rocha et al, 2018). Conversely, sedentary behaviour (SB), which is recognized as any waking behaviour in a sitting/lying posture with very low energy expenditure (Tremblay et al, 2017), has been found to be associated with adverse health outcomes (Copeland et al, 2017) and increased risk of mortality (Ekelund et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This proportion should increase to 25% in the coming decade (Economic and Financial Affairs, 2018). Regular physical activity (PA) is considered a basic element of healthy and independent ageing (Rocha et al, 2018). Conversely, sedentary behaviour (SB), which is recognized as any waking behaviour in a sitting/lying posture with very low energy expenditure (Tremblay et al, 2017), has been found to be associated with adverse health outcomes (Copeland et al, 2017) and increased risk of mortality (Ekelund et al, 2016).…”
Section: Introductionmentioning
confidence: 99%